A research agenda for care coordination for chronic conditions: aligning implementation, technology, and policy strategies. Issue 3 (23rd May 2018) - Kilbourne, Amy M; Hynes, Denise; O'Toole, Thomas; Atkins, David
Abstract: The U.S. healthcare system is changing, spurred on by increasing use of information technologies, changes in legislation and policy, and consumer demand for more convenient, timely, and patient-centered care. However, the current healthcare system is not prepared to maximize the benefits of these changes to optimize health outcomes for patients with chronic conditions, leaving many to fall through the cracks. New models of care coordination that align clinical activities are needed so that patients receive the right care at the right time. The goal of this commentary is to outline a research agenda for care coordination, drawing upon lessons learned from the VA healthcare system in which care coordination is enhanced through the application of health policy, population health/technology, and implementation science. Abstract : This paper describes the current state of care coordination and discusses new research directions that can help patients get the right care at the right time.